The Wildest Lessons Ever! A Book Project in Fifth Grade to Foster Reading Motivation in ELT - Elisabeth Bruckmaier (CLELEjournal, 2018)
In English Language Teaching (ELT) at German secondary schools, work with longer stories and books, including graded readers, usually does not start before seventh or eighth grade, after several years of learning English. In this article, I want to present how fruitful the use of a book - with a plot matching the pupils' interests and a language level fitting their language competencies - can be in the first years of learning English. The evaluation of questionnaires distributed before and after the project demonstrates that with the help of creative and interdisciplinary tasks connected to reading a book, teachers have the opportunity to keep up the pupils' eagerness to learn and to use English, to strengthen their reading motivation, their general language skills, and their creative and social skills. This is due to several reasons, among them the fact that literature integrates content and language, and that intensive and creative work with the reading material leads to a sense of achievement on the part of the pupils.